2021
DOI: 10.1155/2021/8849039
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Radiation Therapy in Ovarian Cancer: A SEER Database Analysis

Abstract: Background and purpose. A large sample size study on survival analysis of radiotherapy in ovarian cancer is deficient. This study aimed to explore the survival impact of radiotherapy in ovarian cancer. Materials and methods. Data of patients diagnosed with ovarian cancer between 2010 and 2015 were collected from Surveillance, Epidemiology, and End Results (SEER) Database. Survival comparisons were analyzed using Kaplan–Meier analysis and log-rank tests. Univariate and multivariate Cox regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…However, a recent study revealed that RT has an adverse effect on the prognosis of patients diagnosed with ovarian cancer. 31 We speculated that RT was more commonly administered to ovarian cancer patients with nonepithelial type, distant metastases, and AJCC stages III/IV, so the poor prognosis may be attributed to a more malignant phenotype in the RT group. Thus, further subgroup and stratification analyses are required in any study.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study revealed that RT has an adverse effect on the prognosis of patients diagnosed with ovarian cancer. 31 We speculated that RT was more commonly administered to ovarian cancer patients with nonepithelial type, distant metastases, and AJCC stages III/IV, so the poor prognosis may be attributed to a more malignant phenotype in the RT group. Thus, further subgroup and stratification analyses are required in any study.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery and platinum-based chemotherapy are the main treatments for ovarian cancer, and 70% of ovarian cancer patients present with metastases at the time of diagnosis, 80-90% of whom have missed surgery [107]. Therefore, cisplatin (DDP)-based chemotherapy is an important approach for the treatment of ovarian cancer.…”
Section: Response To Chemotherapymentioning
confidence: 99%
“…The amount of residual disease following debulking surgery is a significant prognostic indicator for patients [ 8 ]. One study based on Surveillance, Epidemiology, and End Results (SEER) database showed that radiotherapy may be associated with a poorer prognosis in patients with primary ovarian cancer compared to those who do not receive radiation therapy [ 9 ]. In the study of Teckie et al, radiotherapy was considered an efficacious treatment for brain metastases of epithelial ovarian cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%